2020
DOI: 10.1101/2020.04.28.065086
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Associations Between Resting State Functional Connectivity and a Hierarchical Dimensional Structure of Psychopathology in Middle Childhood

Abstract: Background: Previous research from the Adolescent Brain Cognitive Development (ABCD) study delineated and validated a hierarchical 5-factor structure with a general psychopathology ('p') factor at the apex and five specific factors (internalizing, somatoform, detachment, neurodevelopmental, externalizing) using parent-reported child symptoms. The current study is the first examining associations between dimensions from a hierarchical structure and resting state functional connectivity (RSFC) networks.Methods: … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…The current findings also are consistent with recent neuroimaging research, which has found structural and functional alterations in frontoparietal, default mode, visual association cortex, and cerebello-thalamo-cerebro-cortical neural circuits involved in executive control in those high in p ( Elliott et al, 2018 ; Karcher et al, 2020 ; Moberget et al, 2019 ; Romer et al, 2019 , 2018 ; Romer and Pizzagalli, 2021 ; Sato et al, 2016 ). An important next step will be to determine whether structural and functional alterations in these neural circuits prospectively predict future general psychopathology and whether those relations are mediated by executive dysfunction.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The current findings also are consistent with recent neuroimaging research, which has found structural and functional alterations in frontoparietal, default mode, visual association cortex, and cerebello-thalamo-cerebro-cortical neural circuits involved in executive control in those high in p ( Elliott et al, 2018 ; Karcher et al, 2020 ; Moberget et al, 2019 ; Romer et al, 2019 , 2018 ; Romer and Pizzagalli, 2021 ; Sato et al, 2016 ). An important next step will be to determine whether structural and functional alterations in these neural circuits prospectively predict future general psychopathology and whether those relations are mediated by executive dysfunction.…”
Section: Discussionsupporting
confidence: 92%
“…The hypothesis that poor EF may contribute to the p factor is supported by neuroimaging and genetics research as well. Specifically, structural and functional neural abnormalities in frontoparietal, default mode, visual association, and cerebello-thalamo-cerebro-cortical circuits involved in cognitive control have been identified in transdiagnostic meta-analyses ( Goodkind et al, 2015 ; McTeague et al, 2017 ; Sha et al, 2019 ; Shanmugan et al, 2016 ) and in studies of the neural correlates of the p factor ( Elliott et al, 2018 ; Karcher et al, 2020 ; Moberget et al, 2019 ; Romer et al, 2019 , 2018 ; Sato et al, 2016 ; Snyder et al, 2017 ). Shared genetic influences on EF, cognitive function, and transdiagnostic psychopathology in youth twins also has been identified ( Alnæs et al, 2018 ; Grotzinger et al, 2019 ; Harden et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with our findings, previous transdiagnostic studies have reported common disrupted patterns of functional connectivity across mental disorders (Baker et al, 2019; Barron et al, 2020; Ma et al, 2020; Qi et al, 2020; Xia et al, 2018). Moreover, recent studies have demonstrated that the overall psychopathology factor is associated with abnormalities of both within- and between-network functional connectivity (Elliott et al, 2018; Karcher et al, 2020; Kebets et al, 2019). However, these studies calculated functional connectivity by applying a group-level functional atlas to each individual.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, using functional MRI, trans-diagnostic studies have reported dysfunction of association networks across diagnoses (Sha et al, 2019), which may reflect neurobiological correlates of pervasive comorbid psychopathology. Supporting this notion, the burden of overall psychopathology has been linked to abnormal patterns of functional connectivity between large-scale cortical networks (Elliott et al, 2018;Karcher et al, 2020;Kaufmann et al, 2017;Kebets et al, 2019). Nonetheless, it remains unknown whether individual differences in functional topography are related to major dimensions of psychopathology in youth, or whether abnormalities of association cortex topography are linked to overall psychopathology across disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the altered communication between these components may have cascading, detrimental effects on the optimal dynamics of RSNs involved with various cognitive processes ranging from perceptual–attentional to higher-order mental processes. In particular, impaired anticorrelations between the DAN and other networks reflect disrupted functional integration, which may lead to neurodevelopmental problems [ 52 ].…”
Section: Discussionmentioning
confidence: 99%